Ginsenoside F1 administration promotes UCP1-dependent fat browning and ameliorates obesity-associated insulin resistance - Yuhan Meng; Weili Li; Chenxing Hu; Si Chen; Haiyang Li; Feifei Bai; Lujuan Zheng; Ye Yuan; Yuying Fan; Yifa Zhou (Food Science and Human Wellness)
Obesity-induced type 2 diabetes is mainly due to excessive free fatty acids leading to insulin resistance. Increasing thermogenesis is regarded as an effective strategy for hypolipidemia and hypoglycemia. Ginsenoside is a natural active component in Panax ginseng C.A. Meyer, and some of them enhance thermogenesis. However, there are few studies on the mechanism and target of ginsenosides enhancing thermogenesis. Using thermogenic protein uncoupling protein 1 (UCP1)-luciferase reporter assay, we identified ginsenoside F1 as a novel UCP1 activator in the ginsenosides library. Using pull down assay and inhibitor interference, we found F1 binds to β3-adrenergic receptors (β3-AR) to enhance UCP1 expression via cAMP/PKA/CREB pathway. We also investigated the ability of F1 on energy metabolism in obesity-induced diabetic mice, including body weight, body composition and energy expenditure. The results of proteomics showed that F1 significantly up-regulated thermogenesis proteins and lipolytic proteins, but down-regulated fatty acid synthesis proteins. Ginsenoside F1 increased thermogenesis and ameliorated insulin resistance specifically by promoting the browning of white adipose tissue in obese mice. Additionally, ginsenoside F1 improves norepinephrine-induced insulin resistance in adipocytes and hepatocytes, and shows a stronger mitochondria respiration ability than norepinephrine. These findings suggest that ginsenoside F1 is a promising lead compound in the improvement of insulin resistance.